Use of Nanocrystalline Hydroxyapatite With Autologous BMA and Local Bone in the Lumbar Spine: A Retrospective CT Analysis of Posterolateral Fusion Results. Issue 3 (April 2017) - Robbins, Stephen; Lauryssen, Carl; Songer, Matthew N.
Abstract : Study Design: A retrospective, multicenter, medical record review and independent analysis of computed tomographic scans was performed in 46 patients to determine radiographic arthrodesis rates after 1-segment, 2-segment, or 3-segment instrumented posterolateral fusions (PLF) using autograft, bone marrow aspirate (BMA), and a nanocrystalline hydroxyapatite bone void filler (nHA). Objective: To determine the radiographic arthrodesis rates after instrumented lumbar PLF using local autograft, BMA, and nHA. Summary of Background Data: The use of iliac crest autograft in posterolateral spine fusion carries real and significant risks. Many forms of nanocrystalline hydroxyapatite have been studied in various preclinical models, but no human studies have reviewed its efficacy as a bone graft supplement in PLF. Methods: Posterolateral arthrodesis progression was documented approximately 12 months postoperatively using a computed tomographic scan and evaluated by an independent radiologist for the presence of bridging bone. One-year postoperative clinical outcomes were assessed using the PROLO score. Results: Radiographically, 91% patients treated exhibited bilateral or unilateral posterolateral bridging bone. Ninety-four percent of the segments treated exhibited bilateral or unilateral posterolateral bridging bone, whereas 6% segments exhibited no posterolateral bridging bone on either side. A total of 93% individual sites treated exhibited posterolateral bridging bone. In 1-segment, 2-segment, and 3-segment arthrodesis, 88%, 93%, and 100%, respectively, of individual sites exhibited radiographic bridging bone. One-year postoperative PROLO scores for 77% patients were excellent or good. There were no complications related to the posterolateral graft mass and no symptomatic nonunions. Conclusions: The arthrodesis rates after instrumented lumbar fusion using local autograft mixed with BMA and the nHA is equivalent to the rates reported for iliac crest autograft in these indications, including stringent indications, such as 3-segment procedures. By approximately 12 months postoperatively, there was no significant difference in the rates of bridging bone between the 1-segment, 2-segment, and 3-segment procedures.